Characterization and effect of Moringa Oleifera Lam. antioxidant additive on the storage stability of Jatropha biodiesel. (1st December 2020) - Jeyakumar, Nagarajan; Narayanasamy, Bose; Balasubramanian, Dhinesh; Viswanathan, Karthickeyan
Graphical abstract: Abstract: The deterioration of biodiesel during its storage is promoted through oxidation, thus reducing its market value. The storage stability of Jatropha biodiesel produced through the transesterification process can be improved by Moringa Oleifera Lam. (MO) antioxidant addition. The powdered antioxidant was characterized through morphological study using Field Emission Scanning Electron Microscope (FESEM). The elemental analysis of the MO powder was examined using Energy Dispersive X-Ray Spectroscopy (EDS) and CHNS (Carbon, Hydrogen, Nitrogen, and Sulphur) analysis. The presence of antioxidant components like hydroxyl and phenol compounds has been confirmed through Fourier Transform Infrared Spectroscopy (FTIR) analysis. Thermal Analysis of the MO powder was carried out by employing Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA). The characterization of the MO antioxidant was carried out by studying the scavenging effect of free radicals and the presence of phenolic content responsible for it. The scavenging effect was analyzed by means of DPPH (1, 1-diphenyl-2 picryl hydrazyl) assay and the total phenolic content in the antioxidant was determined by Folin-Ciocalteu method. The DPPH inhibition (%) was found to be 29.49, 43.72 and 54.59 at 500, 1000 and 1500 ppm respectively for the ethanol extracts of MO leaves. TPC for MO extract was found to be 112.3 GAE mg/g. The induction time measured using the Rancimat method was 2.29 h and 15.25 h for Jatropha biodiesel and its MO additive at 1500 ppm respectively. Results show that the addition of MO antioxidant has increased the storage stability of Jatropha biodiesel thus increasing its economic value. Importance of the study: The significance of the study arises from the degradation of biodiesel in spite of oxidation due to environmental storage conditions. Novelty of the present study includes the improvement of the oxidation stability of biodiesel by means of Moringa Oleifera Lam . leaves. This natural antioxidant is widely available in tropical countries and it provides an increased economic value. The main objective of the study is to inhibit the oxidation of biodiesel by means of antioxidant addition and improve the storage stability.